2015
DOI: 10.1016/j.polymer.2015.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing response in supramolecular polymers based on reversible zinc–histidine interactions

Abstract: Histidine-metal interactions are utilized in many biological materials as reinforcing crosslinks, and in particular, are believed to contribute as reversible crosslinks to the intrinsic self-recovery behavior of mussel byssal threads. In this contribution, two new histidine-based monomers were synthesized and further copolymerized with butyl methacrylate (BMA) and lauryl methacrylate (LMA) applying the reversible addition–fragmentation chain transfer (RAFT) polymerization technique. Crosslinking with zinc ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 58 publications
5
52
2
Order By: Relevance
“…Examples of metal‐ligand coordination responsible for self‐healing of supramolecular networks: A) ligands are attached to polymer backbones and reversible coordination are formed between (a) dynamic equilibrium of N‐heterocyclic carbenes (NHC) and transition metals monomeric species, (b) polymers containing 2,6‐bis(1‐methylbenzimidazolyl)pyridine (Mebip) ligands coordinated with Zn(NTf) 2 , and (c) terpyridine coordinated with (iron) Fe(II) sulfate; B) ligands are embedded within polymer backbone or as pendent groups and reversible coordination are formed between (a) 2,6‐pyridinedicarboxamide complexed with Fe(III) (B‐2), (b) triazole‐pyridine coordinated with metal salts, (c‐1) tris‐Fe(III)‐catechol complex,[2h] (c‐2) metal‐histidine complex,[42a] (c‐3) metal‐imidazole interactions, and (d) polyethylenimine–copper (II) complex A‐a) Reproduced with permission . Copyright 2007, The Royal Society.…”
Section: Metallosupramolecular Polymersmentioning
confidence: 99%
“…Examples of metal‐ligand coordination responsible for self‐healing of supramolecular networks: A) ligands are attached to polymer backbones and reversible coordination are formed between (a) dynamic equilibrium of N‐heterocyclic carbenes (NHC) and transition metals monomeric species, (b) polymers containing 2,6‐bis(1‐methylbenzimidazolyl)pyridine (Mebip) ligands coordinated with Zn(NTf) 2 , and (c) terpyridine coordinated with (iron) Fe(II) sulfate; B) ligands are embedded within polymer backbone or as pendent groups and reversible coordination are formed between (a) 2,6‐pyridinedicarboxamide complexed with Fe(III) (B‐2), (b) triazole‐pyridine coordinated with metal salts, (c‐1) tris‐Fe(III)‐catechol complex,[2h] (c‐2) metal‐histidine complex,[42a] (c‐3) metal‐imidazole interactions, and (d) polyethylenimine–copper (II) complex A‐a) Reproduced with permission . Copyright 2007, The Royal Society.…”
Section: Metallosupramolecular Polymersmentioning
confidence: 99%
“…Thus, we used poly(pentafluorophenylacrylate)‐ l ‐polydimethylsiloxane (PPFPA‐ l ‐PDMS) precursor conetworks to prepare functionalized APCNs. It has been reported that non‐chelating ligands such as imidazole or histidine form kinetically more labile complexes with metal ions than chelating ligands based on terpyridine or bipyridine, thus leading to better self‐healing behavior. Therefore, pyridine and Zinc(II)‐based complexes were selected as reversible bonds within the polymer conetworks with self‐healing ability.…”
Section: Resultsmentioning
confidence: 99%
“…The last step of metallo‐supramolecular polymer conetworks synthesis consisted in loading metal ions into the APCNs. Zinc(II) was selected because Zn(II) complexes are inherently kinetic labile as demonstrated in previous works on metallo‐supramolecular self‐healing polymers . From a plethora of available Zinc(II) salts, ZnCl 2 was selected due to the high coordinating strength of chloride counter ions, in addition to the fact that they act as bridging ligand, leading to fast self‐healing .…”
Section: Resultsmentioning
confidence: 99%
“…One way to address this issue is to introduce a self-healing mechanism, which has received wide interest both from academia and industry in the last decades. [23][24][25][26][27] For polymers and polymer coatings, most reported self-healing approaches, such as encapsulation, 28,29 reversible bonds/interactions [30][31][32][33][34][35][36][37][38][39][40][41][42] or deformation recovery 43,44 aim at repairing mechanical properties or material integrity. Much less attention has been paid to self-healing mechanisms aiming to recover surface functionalities.…”
Section: -8mentioning
confidence: 99%